The Federal Democratic Republic of Ethiopia : Poverty Reduction Strategy Paper; 2003/04 Annual Progress Report. (IMF Staff Country Reports; Country Report ;, 2006)
This paper examines the Annual Progress Report on the Federal Democratic Republic of Ethiopia's Poverty Reduction Strategy. The broad thrust of the government's strategy remains creating rural growth, accelerating private sector growth in the modern economy to create employment and incomes, and strengthening of public institutions to deliver services. The government has embarked on an aggressive program to accelerate progress as rapidly as possible, including a big push on education to create human capacity, expanding infrastructure as rapidly as financing and capacity will allow, opening the economy, building institutions, and decentralizing government.